2006
DOI: 10.1140/epja/i2006-10109-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlations and characterization of emitting sources

Abstract: Dynamical and thermal characterizations of excited nuclear systems produced during the collisions between two heavy ions at intermediate incident energies are presented by means of a review of experimental and theoretical work performed in the last two decades. Intensity interferometry, applied to both charged particles (light particles and intermediate mass fragments) and to uncharged radiation (gamma rays and neutrons) has provided relevant information about the space-time properties of nuclear reactions. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 133 publications
1
57
0
Order By: Relevance
“…In the case of central collisions, two-fragment correlation functions have been used to extract emission time scales in multifragmentation events, typically observed at intermediate energies [22][23][24][25][26][27]. The extracted emission properties are affected by space-time ambiguities.…”
Section: Recent Exclusive Data Onmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of central collisions, two-fragment correlation functions have been used to extract emission time scales in multifragmentation events, typically observed at intermediate energies [22][23][24][25][26][27]. The extracted emission properties are affected by space-time ambiguities.…”
Section: Recent Exclusive Data Onmentioning
confidence: 99%
“…The extracted emission properties are affected by space-time ambiguities. Moreover, distortions of the correlation function shape induced by momentum and energy conservation laws [28], collective motion and reaction plane orientation effects [29,30], while small or negligible in the case of light particle correlation studies, may become important and difficult to deal with in the case of massive fragment-fragment correlations [24,30].…”
Section: Recent Exclusive Data Onmentioning
confidence: 99%
“…The correlation functions relevant to intensity interferometry investigation [1][2][3][4], however, do not suffer this limitation. Due to their ability to probe the space-time extent of the sources of emission, two particle correlation functions allow a distinction between early dynami-cal and later statistical emission.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…The two-proton correlation function probes the spacial and temporal information about the particle emitting source because the magnitude of the final-state interactions and anti-symmetrization effect depend on both the spacial separation and the relative momentum of particles [4].…”
Section: Two Particle Correlationsmentioning
confidence: 99%
“…These studies have shown that besides nuclei lying close to the stability valley also exotic isotopes are produced in the dynamical phase of the reaction. In particular, the decay properties of the exotic such isotopes of short life-decay time can be studied by measuring the correlation properties of the emitted particles in order to probe valuable spectroscopic information about unbound exotic states that can be isolated by means of this techniques [4][5][6][7][8][9][10]. From this point of view HIC can be viewed not only as a powerful tool to study nuclear dynamics and the evolutive path towards equilibrium configurations but also as a unique terrestrial laboratory to produce several nuclear unbound species in one single experiment and to study same of their spectroscopic properties.…”
Section: Introductionmentioning
confidence: 99%